A homozygous Y443C variant in the RNPC3 is associated with severe syndromic congenital hypopituitarism and diffuse brain atrophy - GÜRAN, TÜLAY (My University, 2022)
Biallelic RNPC3 variants have been reported in a few patients with growth hormone deficiency, either in isolation or in association with central hypothyroidism, congenital cataract, neuropathy, developmental delay/intellectual disability, hypogonadism, and pituitary hypoplasia. To describe a new patient with syndromic congenital hypopituitarism and diffuse brain atrophy due to RNPC3 mutations and to compare her clinical and molecular characteristics and pituitary functions with previously published patients. A 20-year-old female presented with severe growth, neuromotor, and developmental delay. Her weight, height, and head circumference were 5135 gr (-25.81 SDS), 68 cm (-16.17 SDS), and 34 cm (-17.03 SDS), respectively. She was prepubertal, and had dysmorphic facies, contractures, and spasticity in the extremities, and severe truncal hypotonia. There were no radiological signs of a skeletal dysplasia. The bone age was extremely delayed at 2 years. Investigation of pituitary function revealed growth hormone, prolactin, and thyroid-stimulating hormone deficiencies. Whole-exome sequencing revealed a novel homozygous missense (c.1328A > G; Y443C) variant in RNPC3. Cranial MRI revealed a hypoplastic anterior pituitary with diffuse cerebral and cerebellar atrophy. The Y443C variant in RNPC3 associated with syndromic congenital hypopituitarism and abnormal brain development. This report extends the RNPC3-related hypopituitarism phenotype with a severe neurodegenerative presentation.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Natural Sciences; GENETİK VE KALITIM; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); GENETICS & HEREDITY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); Genetik; Moleküler Biyoloji; Genetik (klinik); Genetics; Molecular Biology; Genetics (clinical); brain atrophy; neurodegeneration; neuropathy; RNPC3; syndromic congenital hypopituitarism; MINOR SPLICEOSOME; DEVELOPMENTAL DISORDER; COMPONENT; MUTATION; RNU4ATAC; brain atrophy; neurodegeneration; neuropathy; RNPC3; syndromic congenital hypopituitarism